2006
DOI: 10.1111/j.1369-7625.2006.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Putting informed and shared decision making into practice

Abstract: Objective To investigate the practice, experiences and views of motivated and trained family physicians as they attempt to implement informed and shared decision making (ISDM) in routine practice and to identify and understand the barriers they encounter.Background Patient involvement in decision making about their health care has been the focus of much academic activity. Although significant conceptual and experimental work has been done, ISDM rarely occurs. Physician attitudes and lack of training are identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 21 publications
(36 reference statements)
5
108
0
5
Order By: Relevance
“…4,7,8,10 To the authors' knowledge, one paper has focused on concerns, expectations, and ideas in the context of shared decision making. 11 The study, which used transcripts of medical consultations, indicated that GPs are able to elicit ideas, concerns, and expectations from patients (expectations about diagnosis, but not about management).…”
Section: Methodsmentioning
confidence: 99%
“…4,7,8,10 To the authors' knowledge, one paper has focused on concerns, expectations, and ideas in the context of shared decision making. 11 The study, which used transcripts of medical consultations, indicated that GPs are able to elicit ideas, concerns, and expectations from patients (expectations about diagnosis, but not about management).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that shared decision making training may be more effective if incorporated into undergraduate educational curriculums so that clinicians graduate not just aware, but also with some experience of it, before establishing clinical habits and patient interaction patterns. 11 But we know little about if and when students are taught these skills. For example, a survey of evidence-based medicine curricula in UK medical schools asked about just one element of shared decision making (risk communication), which was taught and practiced in tutorials in only one-quarter of respondent schools.…”
Section: Introductionmentioning
confidence: 99%
“…Whatever definition and measure are used, however, SDM has not been found to be a frequent part of usual medical practice. [7][8][9] It may be particularly important to understand and improve the frequency of SDM for patients with depression who are seen in primary care. Although common in primary care, patients who receive depression treatment in this setting often do not receive the same quality of care that has been shown to be possible in effectiveness studies of depression treatment.…”
mentioning
confidence: 99%